2011 11th IEEE International Conference on Nanotechnology 2011
DOI: 10.1109/nano.2011.6144499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface functional groups on the aggregation stability of magnetite nanoparticles in biological media containing serum

Abstract: -Size stability of magnetite nanoparticles (MNP) with different surface functional groups in biological media was achieved by the addition of fetal bovine serum (FBS). The stability of the particles was attributed to the formation of protein coronas around the particles, which provides sufficient steric hindrance to prevent aggregation of the particles. The stability of different modified MNP were also studied in biological media containing bovine serum albumin (BSA) to further understand the stabilization mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Here, our data showed that InP/ZnS coated with hydroxyl group were more likely to aggregate, and the particle size in the water was far greater than the other QDs coated with carboxyl or amino group. It is mainly because that the hydroxyl groups around the particles couldn’t provide sufficient steric hindrance to counterbalance the attractive Van der Waal forces between particles ( Wiogo et al, 2011 ). Apart from the stability and hydrodynamic size distribution, the surface properties also influence the fluorescence intensity of the QDs.…”
Section: Discussionmentioning
confidence: 99%
“…Here, our data showed that InP/ZnS coated with hydroxyl group were more likely to aggregate, and the particle size in the water was far greater than the other QDs coated with carboxyl or amino group. It is mainly because that the hydroxyl groups around the particles couldn’t provide sufficient steric hindrance to counterbalance the attractive Van der Waal forces between particles ( Wiogo et al, 2011 ). Apart from the stability and hydrodynamic size distribution, the surface properties also influence the fluorescence intensity of the QDs.…”
Section: Discussionmentioning
confidence: 99%